Fracture toughness anisotropy in shale. Issue 3 (31st March 2016) - Chandler, Michael R.; Meredith, Philip G.; Brantut, Nicolas; Crawford, Brian R.
Abstract: The use of hydraulic fracturing to recover shale gas has focused attention on the fundamental fracture properties of gas‐bearing shales, but there remains a paucity of available experimental data on their mechanical and physical properties. Such shales are strongly anisotropic, so that their fracture propagation trajectories depend on the interaction between their anisotropic mechanical properties and the anisotropic in situ stress field in the shallow crust. Here we report fracture toughness measurements on Mancos shale determined in all three principal fracture orientations: Divider, Short Transverse, and Arrester, using a modified short‐rod methodology. Experimental results for a range of other sedimentary and carbonate rocks are also reported for comparison purposes. Significant anisotropy is observed in shale fracture toughness measurements at ambient conditions, with values, as high as 0.72 MPa m 1/2 where the crack plane is normal to the bedding, and values as low as 0.21 MPa m 1/2 where the crack plane is parallel to the bedding. For cracks propagating nonparallel to bedding, we observe a tendency for deviation toward the bedding‐parallel orientation. Applying a maximum energy release rate criterion, we determined the conditions under which such deviations are more or less likely to occur under more generalized mixed‐mode loading conditions. We find for Mancos shale that the fracture should deviate toward the plane with lowest toughness regardless of the loading conditions. Key Points: Mancos shale displays mechanical anisotropy in terms of tensile strength and fracture toughness Ductility for Mancos shale is high, but not significantly higher than for other sedimentary rocks Fractures are commonly seen to deflect into the Short Transverse orientation during experiments